2021
DOI: 10.1128/spectrum.00831-21
|View full text |Cite
|
Sign up to set email alerts
|

Respiratory Pathogen Coinfections in SARS-CoV-2-Positive Patients in Southeastern Wisconsin: A Retrospective Analysis

Abstract: This examination of respiratory pathogen coinfections in SARS-CoV-2 patients will likely shed light on our understanding of polymicrobial infection associated with COVID-19. Our results should prompt public health authorities to improve seasonal respiratory pathogen surveillance practices and address the risk of disease severity.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

9
14
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 18 publications
(27 citation statements)
references
References 33 publications
(51 reference statements)
9
14
0
Order By: Relevance
“…In this study, based in Jordan, 38.3% of patients were positive for both SARS-CoV-2 and HRV. In accordance with the present finding, a recent study in Australia 20 and South-eastern Wisconsin 21 have demonstrated that HRV is the highest frequent SARS-CoV-2 co-infection, representing 63.2% and 41.51%, respectively. The most common co-infection was HRV also in Korea.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…In this study, based in Jordan, 38.3% of patients were positive for both SARS-CoV-2 and HRV. In accordance with the present finding, a recent study in Australia 20 and South-eastern Wisconsin 21 have demonstrated that HRV is the highest frequent SARS-CoV-2 co-infection, representing 63.2% and 41.51%, respectively. The most common co-infection was HRV also in Korea.…”
Section: Discussionsupporting
confidence: 93%
“…A recent study in Australia 20 and South-eastern Wisconsin 21 have demonstrated that HRV is the highest frequent SARS-CoV-2 co-infection, representing 63.2% and 41.51%, respectively. In Turkey, HRV was reported in 14.2% and 10.0% of the COVID-19 cases in men and women, respectively.…”
Section: Introductionmentioning
confidence: 98%
“…[4][5][6] Also, in a retrospective study, the most common coinfected microorganism was found to be Mycoplasma pneumoniae (25%), followed by virus (7%) and bacteria (5%). 7 Similar to previous literature, [2][3][4][5][6] the authors demonstrated four times human rhinovirus (A and B), thrice both human coronavirus (229E and OC43) and mastadenovirus A, and once Influenza A virus. 1 Our patient is 2.1/2-year-old male patient who was followed up with the diagnosis of severe form of transient hypogamma- In very near future, SARS-CoV-2 coinfections with other RTI viruses and other bacterial and fungal microorganisms in human will be discussed more and gain importance to take care of these patients.…”
Section: E T T E R T O T H E E D I T O R Coinfection Between Sars-cov...supporting
confidence: 82%
“…4 , 5 , 6 Also, in a retrospective study, the most common coinfected microorganism was found to be Mycoplasma pneumoniae (25%), followed by virus (7%) and bacteria (5%). 7 Similar to previous literature, 2 , 3 , 4 , 5 , 6 the authors demonstrated four times human rhinovirus (A and B), thrice both human coronavirus (229E and OC43) and mastadenovirus A, and once Influenza A virus. 1 …”
supporting
confidence: 86%
See 1 more Smart Citation